Software livre para implementação de clusters de alta disponibilidade - ROCHA, Edgar da (004, 2003)
Este trabalho apresenta os principais aspectos de alta disponibilidade cujo objetivo é a manutenção da operação de serviços oferecidos pelos sistema computacionais, em caso de erros no sistema. também demonstra as principais funcionalidade presentes nos software analisados, fornecendo subsídios para futuras implementações de clusters de alta disponibilidade

This work presents the main aspects of high availability whose objective is to maintain the operation of services offered by computer systems, in case of errors in the system. it also demonstrates the main functionality present in the analyzed software, providing subsidies for future implementations of high availability clusters
Free software for implementing high availability clusters
Keywords: Software livre; Clusters; Informação e Comunicação